2022
DOI: 10.3390/toxics10100558
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Skin Irritation of Acids Commonly Used in Cleaners in 3D-Reconstructed Human Epidermis Model, KeraSkinTM

Abstract: Cleaners such as dishwashing liquids contain various chemicals that cause skin damage. Alkaline agents used in cleaners alter the lipid composition of the skin and damage the skin barrier. However, little is known about the effects of acids used in cleaners on the skin. Here, we investigated the effects of acidic pH on the skin and evaluated the skin irritation of acids commonly used in cleaners with a 3D-reconstructed human epidermis model, KeraSkinTM, according to OECD TG439. First, to examine the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Lactic acid is used in the green cleaning industry as a descaling and antimicrobial agent, which is produced by fermentation based on natural and renewable resources, and is an alternative to synthetic agents such as inorganic acids. 50…”
Section: Resultsmentioning
confidence: 99%
“…Lactic acid is used in the green cleaning industry as a descaling and antimicrobial agent, which is produced by fermentation based on natural and renewable resources, and is an alternative to synthetic agents such as inorganic acids. 50…”
Section: Resultsmentioning
confidence: 99%
“…The irritating potential of succinic acid as potential ingredient of cleaners has been studied by Hwang et al (2022). The test of skin irritation in 3D-reconstructed human epidermis model shown that exposition to succinic acid at the concentration of 0.1 mol/dm 3 caused no significant decrease in cell viability.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the stratum corneum is the key to maintaining skin barrier function and xenobiotic metabolism [ 17 ]. Accordingly, the structural integrity of the stratum corneum is closely linked to resistance to skin irritation [ 18 ] and the development of skin diseases [ 19 ]. The epidermis of RHE [ 14 ] and ex vivo skin models from animals consists of the same epidermal layers as found in humans [ 20 ].…”
Section: Discussionmentioning
confidence: 99%